If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(9 + 5v) = -19 (9 * 6 + 5v * 6) = -19 (54 + 30v) = -19 Solving 54 + 30v = -19 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 30v = -19 + -54 Combine like terms: 54 + -54 = 0 0 + 30v = -19 + -54 30v = -19 + -54 Combine like terms: -19 + -54 = -73 30v = -73 Divide each side by '30'. v = -2.433333333 Simplifying v = -2.433333333
| 20=0.16x-1.28y | | X=-5.75 | | y=500+0.5y | | 6(7d-3)=-29 | | .50+0.5x=2.50 | | 72=3x+14 | | 9k+2=3k-22 | | 4ab+3ba= | | 8x-2(x+4)=10 | | 0=-16t^2+41t+209 | | ln(3x)=3ln(x) | | 345(x+75)=45 | | 2x=3+-0.5y | | 9j-7+3j=6j-10j+3j | | .25+0.5x=2.25 | | -5(-3x+2)-2=2 | | 6k+2=2k-14 | | -5(-3x+2)-2=-2 | | -7x+4=-6x+1 | | 5(2x+4)-3=3 | | 49x-20x-10=0 | | (3x-4)+2=1 | | 2x=-6+-12 | | 2(x+4+3)=6 | | 6+-12=6 | | -5m+6=-8m+3(-8-4m) | | 6(1+5y)=(m-2) | | -3(x-3)+3=6 | | 6x-10+3x=0 | | -8(-x-6)+10=-2 | | 1208-41x=14x+53 | | -8(-x-6)+10=2 |